International bond issues of the less-developed countries : diagnosis and prescription - Cheng, Hang-sheng (Ames : Iowa State University Press, 1969)
The book seeks to address two questions: first, why have the international bond issues of the less-developed countries since the end of the 2nd World War been so small both in absolute amounts and by comparison with their volumes in the 1920s? And second, what can be done to help bring back a vigorous revival of the international market of these issues and at the same time to provide a safeguard against recurrences of the ills that so plagued the market in the past?
Includes bibliographical footnotes.
oif 28/01/2019
Loans
Keywords: Bonds; Finance; International finance; World Bank